Mutuo project : estrategia de sostenibilidad para hoteles en Barú (2017)
"Colombia is a country that has been characterized by its terrestrial and marine biodiversity. On the Caribbean coast we have one of the most important coral reefs, accounting for 77% of all corals in the entire country... with the boom of the tourist industry in this area and The lack of control, up to date can be entering up to 13,000 (Madrid, 2017) that generate approximately 7 tons of garbage in a single weekend. The impact of this disproportionate number of tourists has been causing irreparable damage to one of the most important ecosystems not only for the local community, for the country and for the world. The project seeks to integrate into a strategy the various actors who have played a major role in the degradation and giving greater capacity for reaction to the ecosystem and the entities and people that watch over its conservation and care." -- Tomado del Formato de Documento de Grado.